Viral Marketing Pada Usaha Mikro Kecil Menengah (UMKM) Halal - Faisal Hamdani Harahap; Iqbal Fahri Tobing; Muhammad Suhaimi; Maryam Batubara (ITB AAS INDONESIA Surakarta, 2023)
Viral is a term that is always associated with content on social media. Content that has gone viral often has a certain appeal which makes social media users like the activity of re-sharing/re-posting that content. The existence of this phenomenon has become a separate strategy in digital marketing, especially on social media, namely viral marketing. according to data from the Ministry of Cooperatives and UKM that there are still many UMKM actors, including Halal UMKM, who have not yet approached technology in their marketing, this can be seen from the percentage figure which has only reached 13% of UMKM adopting digital technology. This study aims to identify and describe viral marketing as a strategy in digital marketing through social media. This study uses a qualitative-descriptive research method with a literature study data collection method. The results of this study indicate that creative and innovative content is a component of viral marketing, thereby creating a culture of content sharing. On the other hand, the influencer/buzzer role also influences viral marketing as a digital marketing strategy. The phenomenon of the virality of content on social media has had a significant impact and is used as the latest strategy method for UMKM actors.